1992
DOI: 10.1128/cmr.5.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral therapy: current concepts and practices

Abstract: Drugs capable of inhibiting viruses in vitro were described in the 1950s, but real progress was not made until the 1970s, when agents capable of inhibiting virus-specific enzymes were first identified. The last decade has seen rapid progress in both our understanding of antiviral therapy and the number of antiviral agents on the market. Amantadine and ribavirin are available for treatment of viral respiratory infections. Vidarabine, acyclovir, ganciclovir, and foscarnet are used for systemic treatment of herpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 511 publications
(372 reference statements)
0
29
0
2
Order By: Relevance
“…Ganciclovir inhibits viral replication and its efficiency depends on its commencement [18], Studies carried out on the murine CMV models have demonstrated that the drugs which most enhance reactivation of latent viruses are antilymphocvtic globulins and steroids, followed by azathioprine and cyclophosphamide [19], Although cy closporine is not able to reactivate latent viruses, it inhib its the cytotoxic CMV-specific T-cell response, which is a major defense against viral infection. In this way, sequen tial therapies based on OK.T3, prednisone, azathioprine and cyclosporine, as is our case, enhance the risk of symp tomatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Ganciclovir inhibits viral replication and its efficiency depends on its commencement [18], Studies carried out on the murine CMV models have demonstrated that the drugs which most enhance reactivation of latent viruses are antilymphocvtic globulins and steroids, followed by azathioprine and cyclophosphamide [19], Although cy closporine is not able to reactivate latent viruses, it inhib its the cytotoxic CMV-specific T-cell response, which is a major defense against viral infection. In this way, sequen tial therapies based on OK.T3, prednisone, azathioprine and cyclosporine, as is our case, enhance the risk of symp tomatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for HCMV diseases remain limited and currently available therapies have significant toxicity (Bean, 1992). Moreover, clinically isolated HCMV strains that are resistant to the conventional drugs are becoming increasingly common (Baldanti et al, 1996 ;Chou et al, 1995).…”
Section: Dhfr Induction By MCMV Dhfr Induction By Mcmvmentioning
confidence: 99%
“…Some studies have supported a role for both immunoregulatory and antiviral therapies in the treatment of myocarditis. Until now, few effective drugs have been available to treat the disease, and severe cases have a poor prognosis without heart transplantation [11,12]. To treat viral myocarditis, ribavirin (RB) has been found to exhibit potent antiviral properties vital for the clinical treatment of viral diseases [13]; however, its use remains controversial because of its questionable efficacy, side effects, and high cost.…”
Section: Introductionmentioning
confidence: 99%